Silicotungstate-modified zirconia as an efficient catalyst for phenol tert-butylation - Devassy, Biju M.; Shanbhag, G. V.; Mirajkar, Subhash P.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2005)
The alkylation of phenol with tert-butanol was investigated using zirconia modified with silicotungstic acid (STA) as catalysts. The catalysts with different STA loading (5-25 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 350 to 850 degrees C) were prepared and characterized by X-ray diffraction and NH3-TPD measurements. The XRD results indicate that STA stabilizes the tetragonal phase of zirconia. The catalyst with 15% STA on ZrO2 calcined at 750 degrees C shows the highest acidity and hence highest activity. Under the reaction conditions of 140 degrees C, tert-butanol/phenol molar ratio of 2 and LHSV of 4 h(-1), phenol conversion was 95.4% with selectivity to 2-tert-butyl phenol 4.3%, 4-tert-butyl phenol 59.2% and 2,4-di-tert-butyl phenol 35.8%. The reaction was studied as a function of time for 50 It without appreciable change in phenol conversion and product selectivity. The deactivated catalyst could be regenerated by calcination with out appreciable lose in catalytic activity and product selectivity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: phenol; Silicotungstic acid; tert-butylation; Zirconia

Synthesis of linear alkyl benzenes over zirconia-supported 12-molybdophosphoric acid catalysts - Devassy, Biju M.; Lefebvre, F.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The liquid-phase alkylation of benzene with 1-octene and 1-dodecene was investigated using zirconia-supported 12-molybdophosphoric acid (MPA) as catalyst. The catalysts with different MPA loading (5-25 wt.% calcined at 700 degrees C) and calcination temperature (15 wt.% calcined from 500 to 750 degrees C) were prepared by suspending zirconium oxyhydroxide in methanol solution of MPA followed by drying and calcination. These catalysts were characterized by X-ray diffraction, and P-31 MAS NMR spectroscopy measurements. The XRD results indicated that MPA stabilizes the tetragonal phase of zirconia. 3 1 P MAS NMR spectra show that the nature of phosphorous species depend on MPA loading and calcination temperature, and it show the existence of three types of phosphorous species, one is the Keggin unit and the other is the decomposition product of MPA and third one an unidentified species. FTIR pyridine adsorption on 15% MPA catalyst calcined at 700 degrees C showed the presence both Bronsted and Lewis acidity. Under the reaction conditions of 83 C, benzene/1-olefin molar ratio of 10 (time, 1 h), the most active catalyst, 15% MPA calcined at 700 C gave more than 90% olefin conversion with selectivity to 2-phenyl octane, 55% and 2-phenyl dodecane, 45%. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 12-molybdophosphoric acid; benzene alkylation; linear alkyl benzene; Zirconia

Shape selective synthesis of long-chain linear alkyl benzene (LAB) with AIMCM-41/beta zeolite composite catalyst - Bordoloi, Ankur; Devassy, Biju M.; Niphadkar, P. S.; Joshi, P. N.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
The liquid-phase alkylation of benzene with long-chain olefins such as 1-decene, 1-octene and 1-dodecene was carried out over AIMCM-41/Beta zeolite composite material as catalyst. The catalyst was prepared by seeding method and characterized by XRD, N-2 sorption, FTIR pyridine adsorption, NH3-TPD and SEM. Powder XRD of AlMCM-41/Beta zeolite composite material showed the co-existence of well-structured microporous and mesophase of AlMCM-41. The typical textural characteristics of micro- and meso-structured phases were observed in the composite material. The effect of temperature, reactant molar ratios and catalyst weight on 1-dodecene conversion and products selectivity was studied. The composite catalyst was found to be the highly selective towards the formation 2-dodecylbenzene. Under the reaction conditions of 120 degrees C, benzene/1-dodecene molar ratio 10 and time 2h, the catalyst gave 48% dodecene conversion with 76%, 2-dodecylbenzene selectivity. Significant improvement in catalytic activity has been achieved by composite material as compared to Al-MCM-41. Although zeolite beta and composite material gave similar conversion of dodecene, the composite material showed higher selectivity towards 2-dodecylbenzene, which could be due to higher diffusibility of 2-dodecylbenzene isomer in the composite material. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: AIMCM-41/beta zeolite composite; Alkylation; Benzene; long-chain olefins

Synthesis, characterization, and molecular modeling studies of novel polyurethanes based on 2,2 '-[ethane-1,2-diylbis(nitrilomethylylidene)]diphenol and 2,2 '-[hexane-1,6-diylbis(nitrilomethylylidene)]diphenol hard segments - Raghu, A. V.; Gadaginamath, G. S.; Jawalkar, S. S.; Halligudi, Shivaraj B.; Aminabhavi, T. A. (Journal of Polymer Science Part A-Polymer Chemistry, 2006)
Novel polyurethanes (PUS) based on 2,2 `-[ethane-1,2-diylbis(nitrilomethylylidene)]diphenol and 2,2 `-[hexane-1,6-diylbis(nitrilomethylylidene)]diphenol as hard segments containing four aromatic diisocyanates (4,4 `-diphenylmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate) have been prepared. Fourier transform infrared, UV spectrophotometry, fluorescence spectroscopy, H-1 NMR and C-13 NMR spectroscopy, thermogravimetric analysis, and differential thermal analysis have been used to determine the structural characterization and thermal properties of the segmented PUS. All the PUS contain domains of both semicrystalline and amorphous structures, as indicated by X-ray diffraction. The acoustic properties have been calculated with the group contribution method. Molecular dynamics simulations have been performed on all the PUS to estimate the cohesive energy density and solubility parameter values, which compare well with the values calculated with the group contribution method. Furthermore, the simulation protocols have been applied to the PUS to produce X-ray diffraction plots to determine the phase morphology of the PUS. The surface properties of the PUS have been estimated from the simulation protocols. (c) 2006 Wiley Periodicals, Inc.
Keywords: amorphous; hard segments; molecular dynamics; Morphology; polyurethanes; Schiff base containing polymers; Thermal properties

Selective oxidation of anthracene using inorganic-organic hybrid materials based on molybdovanadophosphoric acids - Bordoloi, Ankur; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2007)
{Inorganic-organic hybrid materials were synthesized by immobilization of molybdovanadophosphoric acids onto mesoporous silicas, such as MCM-41, MCM-48, and SBA-15, through an organic linker. 12-Molybdovanadophosphoric acids of the general formula H3+xPMO12-xVxO40 (x = 0-3).nH(2)O, such as H-4[
Keywords: EPDM; Photostabilization; polymeric HALS

Synthesis and characterization of novel polyurethanes based on 4,4 `-[1,4-phenylenedi-diazene-2,1-dlyl] bis(2-carboxyphenol) and 4,4 `-[1,4-phenylenedi-diazene-2,1-diyl] bis(2-chlorophenol) hard segments - Raghu, A. V.; Gadaginamath, G. S.; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Reactive & Functional Polymers, 2007)
Eight novel polyurethanes (PUs) based on 4,4'-[1,4-phenylenedi-diazene-2,1-diyl]bis(2-carboxyphenot) and 4,4'-[1,4phenylenedi-diazene-2,1-diyl]bis(2-chloro- phenol) as hard segments with four diisocyanates viz., 4,4-diphenyl-methane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate were prepared. Structural and thermal characterization of the segmented PUs were determined by FT-IR, UV spectrophotometry, fluoroscence spectroscopy, H-1 NMR, C-13 NMR spectroscopy and DTA/TGA analysis. All the PUs contain domains of semi-crystalline and amorphous structures, as indicated by X-ray diffraction. PUs were soluble in polar aprotic solvents like N-methyl-2-pyrrolidone (NMP), dimethyl formamide (DMF) and dimethylsulfoxide (DIVISO). (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: azo polymers; fluorescence; hard segments; Morphology; phase separation; polyurethanes; spectroscopy; Thermal properties

Synthesis, characterization, and acoustic properties of new soluble polyurethanes based on 2,2 `-[1,4-phenylenebis(nitrilomethylylidene)diphenol and 2,2 `-[4,4 `-methylene-di-2-methylphenylene-1,1 `-bis(nitrilomethylylidene)]diphenol - Raghu, A. V.; Gadaginamath, G. S.; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
Eight novel polyurethanes based on 2,2'-[1,4-phenylenebis(nitrilomethylylidene)]diphenol and 2,2-[4,4'methylene-di-2-methylphenylene-1,1'-bis(nitrilomethylylidene) ]diphenol acting as hard segments with two aromatic and two aliphatic diisocyanates (4,4'-diphenytmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate) were prepared and characterized with Fourier transform infrared, UV spectrophotometry, fluorescence spectroscopy, H-1-NMR and C-13-NMR spectroscopy, thermogravimetric analysis, and differential thermal analysis. All the polyurethanes contained domains of semicrystalline and amorphous structures, as indicated by X-ray diffraction. The acoustic properties and solubility parameters were calculated with the group contribution method. (c) 2007 Wiley Periodicals, Inc.
Keywords: infrared spectroscopy; NMR; phase behavior; polyurethanes; Thermal properties

Sol-gel synthesis of MoO(3)/SiO(2) composite for catalytic application in condensation of anisole with paraformaldehyde - Amrute, Amol P.; Bordoloi, Ankur; Lucas, Nishita; Palraj, K.; Halligudi, Shivaraj B. (Catalysis Letters, 2008)
MoO(3)/SiO(2) composite with varying amounts of MoO(3) loading (1-20 wt.%) were prepared by sol-gel method and calcined at 500 C. These catalysts were employed for the liquid phase condensation of anisole with paraformaldehyde. All the catalysts were characterized by N(2) sorption, XRD, and NH(3)-TPD. The activities of synthesized MoO(3)/SiO(2) catalysts were compared with p-toluene sulfonic acid (p-TSA), the most frequently used catalyst for the condensation reactions, and with a supported metal oxide (WO (x) /ZrO(2)). Under the similar reaction conditions, synthesized 10 wt.% MoO(3)/SiO(2) catalyst calcined at 500 C was found to be the most active in the condensation of anisole with paraformaldehyde.
Keywords: 4; 4'-Dimethoxydiphenylmethane; Condensation of anisole; MoO(3)/SiO(2) composites; Paraformaldehyde; Sol-gel synthesis

Studies in structural characterization and correlation with the catalytic activity of an efficient and stable WOx/SBA-15 nanocomposite catalyst - Bordoloi, Ankur; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
A new WOx/SBA-15 nanocomposite catalyst system was developed by hydrothermal synthesis. The material was characterized by X-ray diffraction, high-resolution transmission electron microscopy, sorption analysis, FT-IR, CP-MAS NMR, XPS, and energy-dispersive X-ray analysis. Various types of aromatic and aliphatic sulfides were selectively oxidized to sulfoxides in good to excellent yields without becoming overoxidized to the sulfones using 70% aq. tert-butyl hydrogen peroxide in the presence of nanocomposite catalyst at room temperature. The catalyst could be easily recovered and reused for at least eight reaction cycles under the reaction conditions described here with no significant loss of reactivity. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: catalytic oxidation; mesoporous materials; Sulfides; Sulfoxides; tungsten oxide nanocluster

Synthesis of novel 2-alkyl substituted oleobenzimidazole derivatives using ethylene glycol as solvent - Hosamani, K. M.; Hiremath, V. B.; Keri, R. S.; Harisha, R. S.; Halligudi, Shivaraj B. (Canadian Journal of Chemistry-Revue Canadienne De Chimie, 2008)
The objective of this research was to conduct constructive organic chemistry by using ethylene glycol as an efficient solvent and to achieve yields that were comparable to or better than those in other media. The reaction parameters, such as temperature (150-200 degrees C), density, and reaction time (6 h), have been systematically studied to understand whether ethylene glycol is as an efficient solvent and can have a positive effect on the chemistry with good yields. By tuning the parameters, the yields have been optimized to around 70%-80%. Thus, a new class of 2-alkyl substituted oleo-benzimidazole derivatives have been synthesized and characterized by FTIR, (1)H NMR, (13)C NMR, MS, and elemental analysis.
Keywords: ethylene glycol; oleo-benzimidazole derivatives; oleochemistry; unusual fatty acids

Synthesis and characterization of novel schiff base polyurethanes - Raghu, A. V.; Gadaginamath, G. S.; Jeong, Han Mo; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2009)
Eight different types of novel polyurethanes (PUs) were synthesized through the polyaddition reaction of 4,4'-(ethane-1,2-diylidenedinitrilo)diphenol and 4,4'(pentane-1,5-diylidenedinitrilo)diphenol with four different diisocyanates: 4,4'-diphenylmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate. The resulting PUs were soluble in polar, aprotic solvents. Structures of the diols and PUs were established with Ultraviolet-visible, fluorescence, Fourier transform infrared (FTIR), (1)H-NMR, and (13)C-NMR spectroscopy data. FTIR and NMR spectral data indicated the disappearance of both hydroxyl and isocyanate groups in the PUs. The thermal properties were investigated with thermogravimetry and differential scanning calorimetry. The weight losses, glass transitions, onset temperatures, and crystalline melting temperatures were measured. All the PUs exhibited semicrystalline and amorphous morphologies, as indicated by X-ray diffraction. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 113: 2747-2754, 2009
Keywords: amorphous; Morphology; polyurethanes; synthesis; Thermal properties

Synthesis of chiral sulfoxides by enantioselective sulfide oxidation and subsequent oxidative kinetic resolution using immobilized Ti-binol complex - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2009)
Chiral Ti-binol complex was immobilized onto ionic liquid modified SBA-15 and characterized by different physicochemical techniques. The catalyst was found to be highly enantioselective in the heterogeneous asymmetric oxidation of prochiral sulfides to sulfoxides and subsequent oxidative kinetic resolution of the sulfoxides using aqueous tert-butylhydroperoxide as the oxidant. A positive non-linear effect was observed in the oxidation-kinetic resolution of thioanisole using this supported catalyst. The supported catalyst was reused in multiple catalytic runs without any loss of enantioselectivity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Kinetic resolution; Mesoporous silica; Non-linear effect; Sulfides; Sulfoxides; Supported ionic liquid; Ti-binol